Analysis and evaluation of defensive team strategies in women`s beach volleyball - An efficiency-based approach - Seweryniak, T.; Mroczek, D.; Lukasik, L. (Human Movement, 2013)
Purpose. The aim of this study was to analyze and evaluate beach volleyball defensive strategies in terms of how often various tactics were employed, their effectiveness, reliability, and overall efficiency based on a sample of elite female volleyball players. Methods. A sample of 746 defensive actions performed by various teams that competed in the 2008 Summer Olympic Games (Beijing, China), the 2009 World Championships (Stavanger, Norway), and the 2009 and 2010 Swatch FIVB Beach Volleyball World Tour (Stare Jablonki, Poland; Seoul, South Korea) were analyzed in terms of what defensive systems were employed and their outcomes. Results. Fourteen different defensive systems were used by the teams during defensive play. Out of the fourteen systems, four accounted for almost 75% of all defensive action. The most commonly used defense strategies were selected for more detailed analysis in terms of their activity, effectiveness, and reliability. Conclusions. One defensive system in particular was found to be the most prominent in terms of being the most commonly used as well as efficient among all of the observed systems; high-level teams should place additional focus on mastering this system. Nevertheless, effective team strategy should also include less commonly used systems as a way to take an opponent by surprise by the use of non-standard strategy.